Regional Localization of Suspensor mRNAs during Early Embryo Development - Weterings, Koen (American Society of Plant Biologists, 2001)
We investigated gene activity within the giant embryos of the scarlet runner bean (Phaseolus coccineus) to gain understanding of the processes by which the apical and basal cells become specified to follow different developmental pathways after division of the zygote. We identified two mRNAs, designated G564 and C541, that accumulate specifically within the suspensor of globular-stage embryos. G564 mRNA accumulates uniformly throughout the suspensor, whereas C541 mRNA accumulates to a higher level within the large basal cells of the suspensor that anchor the embryo to the surrounding seed tissue. Both G564 and C541 mRNAs begin to accumulate shortly after fertilization and are present within the two basal cells of embryos at the four-cell stage. In contrast, at the same stage, these mRNAs are not detectable within the two descendants of the apical cell. Nor are they detectable within cells of the embryo sac before fertilization, including the egg cell. We used a G564/β-glucuronidase reporter gene to show that the G564 promoter is activated specifically within the basal region and suspensor of preglobular tobacco embryos. Analysis of the G564 promoter identified a sequence domain required for transcription within the suspensor that contains several copies of a conserved motif. These results show that derivatives of the apical and basal cells transcribe different genes as early as the four-cell stage of embryo development and suggest that the apical and basal cells are specified at the molecular level after division of the zygote.